Accounting under Pressure: A Behavioural Perspective on Financial Targets, Rationalization, and Fraudulent Reporting - Hikmawati, Yuke; Maryani, Neni (E-Jurnal Akuntansi, 2025)
Financial statement fraud, while relatively infrequent, remains the most detrimental form of financial misconduct in terms of the magnitude of losses incurred. This study investigates the extent to which financial targets, external pressure, and rationalization contribute to the occurrence of financial statement fraud within infrastructure companies listed on the Indonesia Stock Exchange during the period 2019–2023. A purposive sampling approach was employed, resulting in a final sample of 95 firm-year observations. The study applied multiple linear regression analysis to examine the hypothesized relationships. The empirical results indicate that financial targets do not exert a statistically significant influence on fraudulent financial reporting. In contrast, external pressure is negatively associated with financial statement fraud, while rationalization exhibits a positive and significant relationship. Collectively, these three factors demonstrate a simultaneous effect on the likelihood of fraudulent reporting. These findings underscore the importance of strengthening risk management frameworks and enhancing internal oversight mechanisms within the infrastructure sector. The results also suggest that cognitive and contextual pressures continue to shape the ethical boundaries of financial reporting behaviour, necessitating greater attention to organizational and psychological drivers of misconduct.  Keywords: Financial Targets; External pressure; Rationalization; Financial Statement Fraud